HEAVY METALS ACCUMULATION POTENCY OF ASPERGILLUS NIGER AND ASPERGILLUS FLAVUS INDIGENOUS TO PAPER MILL EFFLUENT - C. K. SHIVAKUMAR; B. THIPPESWAMY; M. KRISHNAPPA; K. S. ANANTHAMURTHY (The Bioscan, 2011)
This study aimed to reduce Cu2+, Zn2+, Cr6+, Cd2+, Ni2+ and Pb2 heavy metals present in effluent and aqueous medium using Aspergillus niger and Aspergillus flavus isolated from paper mill effluent. Physicochemical content for untreated and treated paper mill effluent was analyzed. 6 heavy metals on fungal growth, morphology and uptake were studied. A.niger tolerated and accumulated up to 1000ppm Pb followed by Cu (500ppm), Zn (250ppm) and Cr, Ni (100ppm). Aspergillus flavus tolerated and accumulated up to 1000ppm of Pb, Zn, Ni and 100ppm of Cu. At 100ppm concentration A.niger showed high Pb (75%) uptake followed by Zn (49%), Cu (45%), Cr (41%) and Ni (25%). A.flavus accumulated metals in the order of Pb (82%), Zn (40%), Cu (34%), and Ni (18%). Significant reduction in Cd, Zn, and Pb heavy metals was reported in untreated industrial effluent inoculated with A.niger and A.flavus biomass with respect to industrial treated effluent.